An Empirical Study About the Effects of ‘Business Tax Reformed to VAT’ on Firms’ Bargaining Power: Based on DID Model - Yanling, Wang; Jiaxi, Wang (European Scientific Journal, ESJ, 2019)
This study empirically examines whether the Business Tax reformed to value added tax (VAT) policy has an impact on the bargaining power of reformed industry firms based on Difference-in-Difference (DID) Model by using the A-share companies listed in both Shanghai Stock Exchange and Shenzhen Stock Exchange from 2010-2015. The bargaining power of firms is divided into two parts: the bargaining power of firms when negotiating with their suppliers and the bargaining power of firms when negotiating with their distributors. We find that the policy does have an impact on the bargaining power of reformed industry firms, specifically, the impact of the policy is to reduce firms’ bargaining power when negotiating with suppliers and improve their bargaining power when negotiating with dealers.